ChemInform Abstract: Antiinflammatory Terpenoids from Boswellia ovalifoliolata. Issue 46 (18th November 2014) - Chib, Renu; Kumar, Manjeet; Rizvi, Masood; Sharma, Simmi; Pandey, Anjali; Bani, Sarang; Andotra, Samar S.; Taneja, Subhash C.; Shah, Bhahwal A.
Abstract Ten terpenoids ‐ including one new sesquiterpenoid (I) and two new triterpenoids (II) and (III) ‐ were isolated from the title species.